DEVELOPING FUNCTIONAL LITERACY IN PRIMARY SCHOOL STUDENTS - Anuarbek Akmaral Yerkazykyzy; Nabidullin S. Aibolat (Research Retrieval and Academic Letters, 2025)
This article explores strategies and pedagogical approaches for developing functional literacy in primary school students. Functional literacy encompasses the ability to read, write, communicate, and apply knowledge in real-life contexts, making it a crucial foundation for a child’s academic and social development. The study aims to identify effective methods for enhancing functional literacy and analyze instructional practices through theoretical review and qualitative methodological analysis. Results highlight the importance of active learning, problem-solving tasks, multimodal resources, and integrated literacy instruction across subjects. The findings demonstrate that functional literacy develops most effectively when traditional teaching is combined with interactive, learner-centered techniques. The research underscores the significance of functional literacy for preparing young learners to participate meaningfully in modern society.